Sea Surface Temperature and Ocean Wind Speed Data in the Cyprus region from Sentinel-3 using Sentinel Application Platform (SNAP) and Arc GIS Pro - Kalogirou, Eleftheria; Melillos, George; Hadjimitsis, Diofantos G.; Makri, Despina (My University, 2023)
The ability to measure sea surface temperature allows us to observe the global system and quantify ongoing weather and climate change. Several industries are particularly affected by increased SST the shipping industry, the offshore oil and gas industry, the fishing industry, etc. Knowledge of ocean wind behaviour will enable ship masters to choose routes that avoid heavy seas or high headwinds that may slow the ship's travel, increase fuel consumption, or possibly cause damage to vessels and loss of life. This paper aims to realise the Cyprus region's sea surface temperature and wind speed data. The comparison of results obtained using Sentinel Application Platform (SNAP) and ArcGIS Pro, shows that both tools can be used to realise Sea Surface Temperature and Ocean Wind Speed Data and give satisfactory results.
Keywords: Sea surface temperature; Ocean Wind Speed Data; Sentinel-3; SNAP; ArcGIS Pro